"They don't really care…": Effects of music with prosocial content and corresponding media coverage on prosocial behavior. (September 2018) - Ruth, Nicolas
Many musicians deliver prosocial messages in their music and engage in charity events, but we know very little about how our reception of this music affects us. Following the General Learning Model by Buckley and Anderson, one possible explanation could be that the music affects us because we know about the engagement and the intentions of the musicians. In most cases this knowledge is received through media coverage. Two studies were conducted to investigate what influence media coverage about music with prosocial content has on participants' appraisal of the music, and the effect of the music on participants. The first study ( N = 145) altered the valence of the media coverage about a semi-fictional music charity project in a 3 × 1 between-subjects design. The second study ( N = 157) used music by an unknown artist that had either prosocial or comparable neutral lyrics alongside positive or neutral media coverage about the artist in a 2 × 2 between-subjects design. Both studies tested the extent to which participants' appraisal of the music they listened to, their empathy and associated prosocial behavior or prosocial behavioral intentions differed between experimental groups. Results of Study 1 indicate that media coverage influences our appraisal as negative media coverage of the charity project was found to negatively affect participants' appraisal of that project and Study 2 yielded that neutral media coverage of the unknown artist led to the most positive appraisal of the artist's music.